Research of Syntactic Devices in Uzbekistan Linguistics (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article discusses syntactic devices and their study in Uzbek linguistics. Through the analysis of syntactic devices, attention is paid to the study of sentence structure, ways of connecting words, connectives and syntactic relations. Also, modern research directions and views of linguists in this area are considered.